Separation of Macro Amounts of Metal Pairs, II: Separation of Zinc and Cobalt - Elkot, A.M. (Asian Journal of Chemistry, 2010)
A systematic study was performed on the separation of zinc and cobalt from various concentrations of cadmium, zinc and cobalt in the original aqueous solutions. Recommended separation can be achieved from macro-concentrations of 0.04M Cd2+,0.3M Zn2+ and O.4M Co2+by Amberlite LA–2from 4.5M H2SO4 to 0.16M HBr with respect to the three metals.